The role of leadership towards the continuous learning organization : a study on JKM, MAMPU & DUNS / Mardiana Ahmad and Nur Fifi Suryanie Abd Gani - Ahmad, Mardiana; Abd Gani, Nur Fifi Suryanie (2012)
Globalization that the world faces now requires everyone to equip themselves with any kind of knowledge, information as well as skills. But in organization it requires personnel to take proactive action to learn and leaders can play their roles to inculcate continuous learning organization as leaders need to start the learning as well as sharing process so that others can easily adapt wit it and at the same times leaders must use their power in influencing "Walk the Talk". Sharing knowledge and information is one of the ways in continuous learning as it also can make the learning process into less formal environments where personnel's are sharing, helping and learning together. How leaders' influencing his personnel's along the way also need to be take into consideration as well as the openness and willingness in sharing knowledge information within organization in order to create continuous learning organization. By conducting this research we found that the application of learning organization and the learning culture among the employees from different demographic, some how have create the level of knowledge sharing, for example the education level among the employees. Besides, the application also was able to create positive environment where it would help the employee to get useful knowledge and information. Besides, it also proved that the employment status of the employee is associated with the vary opinion where leaders' influence are the important elements towards continuous learning culture in organization.